CHANGE TRENDS IN THE USE OF PASSENGER CARS ON URBAN TRIPS: CAR-POOLING IN GDYNIA - Katarzyna HEBEL; Marcin WOŁEK (Scientific Journal of Silesian University of Technology. Series Transport)
The wide accessibility of European citizens to cars results in problems caused by their excessive use as a means of urban transport. Given this situation, it is necessary to find new solutions for the more efficient use of passenger cars in cities. This problem affects almost all European cities, including those in Poland. The paper analyses the level of motorization and modal split in Polish cities with county status, while selected European cities serve as a background to determine the scale of the problem. In the search of solutions in relation to Poland, an analysis of different documents outlining the directions of urban mobility was conducted. One of these documents concerned the promotion of car-pooling, the history of which dates back to the Second World War and the 1950s. Initially introduced in the USA, its increasing development in European cities has been witnessed in recent years. Research on the evaluation of real car-pooling in Polish cities was conducted in Gdynia by the authors of this study. The results of marketing research presented in the article have determined the degree to which participants in urban mobility are inclined to take part in car-pooling schemes in Polish cities.